Designing an artefact to help users make intervention decisions about their wellness. (10th June 2016) - Gleasure, Rob; Grace, Audrey
Abstract: Healthcare systems have been evolving towards more decentralised, patient- empowered, and holistic approaches. This places a greater expectation on patients to monitor and report changes in their general wellness so they can make decisions as to when to seek clinical interventions. However, findings from this study suggest individuals find it challenging to detect deteriorations in wellness, due to the vast and multifaceted nature of the concept, the gradual onset of symptoms, and the difficulty in articulating change. Thus a mobile application is developed to help users with these issues. The design of this mobile application draws upon existing cognitive neuroscience research on change detection, both for external stimuli and internal 'interoceptive' sensations. This highlights several key factors to be considered, if wellness-related decision-making is to be supported. In particular, this identifies the role of patients' top-down (attentional) and bottom-up (less-voluntary) processes for detecting wellness deteriorations.